Toripalimab plus chemotherapy versus chemotherapy as first-line therapy for extensive-stage small cell lung cancer: a cost-effectiveness analysis - Zhang, Longfeng; Chen, Hongcai; Zhu, Huide; Zheng, Zhiwei (Frontiers in Immunology, 2025)
ObjectiveThe aim of this study was to evaluate the cost-effectiveness of toripalimab plus chemotherapy compared to chemotherapy alone as first-line therapy for extensive-stage small cell lung cancer(ES-SCLC) from the Chinese medical perspective.MethodsOur study utilized a partitioned survival model to estimate the costs and clinical outcomes for patients with ES-SCLC. The model incorporated direct healthcare costs and clinical outcomes.The primary outcome measures used in our analysis were quality adjusted life year (QALY) and incremental cost-effectiveness ratio (ICER). These measures were employed to evaluate the cost-effectiveness advantage of the treatment strategy by comparing it to the willingness-to-pay (WTP) thresholds. To account for uncertainties in the model results, One-way and probabilistic sensitivity analyses were conducted to assess the uncertainty of the model results.ResultsThe base-case analysis showed that the total cost for toripalimab plus chemotherapy was $50,918.81, while the cost for chemotherapy was $20,280.31.The combination toripalimab therapy led to a higher QALY value of 1.59 compared to 0.55 for chemotherapy. This translated into an ICER of $29,460.09 per QALY gained, which was below the WTP threshold of $40,343.68 per QALY. The results of the sensitivity analyses demonstrated that the findings were not significantly affected by changes in any of the input parameters.ConclusionOur analysis suggests that toripalimab plus chemotherapy is likely to be a cost-effective first-line therapy for ES-SCLC compared to chemotherapy alone, based on the WTP threshold of $40343.68 per QALY.